THE RELEVANCE OF THE ABU DHABI DOCUMENT AS A SUSTAINABILITY OF RELIGIOUS MODERATION IN INDONESIA FROM A HADITH PERSPECTIVE - Daffa, Muhammad (Harmoni, 2023)
Pope Francis and Al-Azhar Grand Imam Ahmad Al-Tayyeb signed the Abu Dhabi Document. On February 4, 2019, they signed the Document of Human Brotherhood for World Peace and Coexistence. Through a hadith perspective, the purpose of this study is to discuss the significance of the Abu Dhabi document as a continuation of religious moderation in Indonesia. Case studies on religious studies were the focus of the qualitative research that took place. The researcher was treated as an outsider in this method. Based on the findings of the research, it is seen that the Abu Dhabi document has significance for the long-term sustainability of religious moderation in Indonesia from the perspective of hadith so that Indonesia can use the Abu Dhabi document as a model of religious moderation. Through hadith, this study offers a new perspective on the Abu Dhabi document. In the context of religious life in Indonesia, traditions on humanity and religious moderation emerge as an essential source of inspiration. As a direction for religious moderation, one alternative is the relevance of the values outlined in the Abu Dhabi document. As a result, this study shows that, from a hadith perspective, the significance of the Abu Dhabi document may be related to the long-term sustainability of religious moderation in Indonesia.